Pelatihan Pembuatan Lembar Kerja Peserta Didik Berbasis Keterampilan Proses Sains Menggunakan Physics Toolbox sebagai Alternatif Keterbatasan Praktikum Fisika: Training to Create Student Worksheet Based on Science Process Skills Using Physics Toolbox as an Alternative to the Limitations of Physics Practicum - Nurjanah, Widia Linta; Maqruf, Ahmad; Aditya, Raldy; Afa, Aghnia Nadhira; Fauziah, Andi; Tanjung, Nur Fatma; Aminudin, Ahmad; Iryanti, Mimin (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Student Worksheet (LKPD) is a learning tool that has a role in activating students in the learning process. This training aims to introduce technology that can support practicum as an optimization of the implementation of Physics practicum activities by utilizing the Physics Toolbox Sensor Suite application. The methods used in this activity include socialization, lectures, and discussions. Participants in this activity were Physics teachers totaling 46 people. This activity was conducted in three meetings. Participants received an introduction to the various features of the Physics Toolbox Sensor Suite application at the first meeting. Expert lecturers guided the trainees in the application of the tool in the second meeting. After receiving guidance, the trainees were directed to make the LKPD which would then be presented at the third meeting. This training produced six LKPDs with six different Physics materials. The results of the LKPD assessment by experts showed a very positive view of the quality of the LKPD. LKPD generated in this training is considered to have fulfilled all indicators of Science Process Skills (KPS). Through this activity, it can be concluded that the KPS-based LKPD assisted by the Physics Toolbox Sensor Suite application can be a practicum tool that facilitates the implementation of Physics practicum in schools that do not have or lack practicum tools. It is recommended that the use of laboratories and virtual laboratories can be conducted continuously to support Physics learning.